2011
DOI: 10.4236/abc.2011.13009
|View full text |Cite
|
Sign up to set email alerts
|

Biological and physiological parameters of <i>Bulinus truncatus</i> snails exposed to methanol extract of the plant <i>Sesbania sesban</i> plant

Abstract: The effects of sublethal concentrations of methanol extract of Sesbania sesban plant on survival rate, egg laying of Bulinus truncatus snails, hatchability of their eggs, infection rate with Schistosoma haematobium miracidia, cercarial production and certain physiological parameters of treated snails were studied. The sublethal concentrations of the tested plant extract (LC 0 , LC 10 and LC 25 ) caused considerable reduction in survival rates; egg production of B. runcates snails; hatchability of eggs as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
6
14
0
Order By: Relevance
“…The authors conjectured that the reason could be disturbances in the activities of the snail enzyme system and the total protein concentration in the tissues and haemolymph which suppressed the development of parasite larval stages in the snail tissues. Similarly, exposure of S. mansoni-infected B. alexandrina to the photosensitiser carbamide perhydrate significantly reduced the cercarial production per treated snail compared to the control snails (Gawish et al 2009). It can be concluded that sub-lethal concentrations of copper chlorophyllin (Cu-chl) and magnesium chlorophyllin (Mg-chl) as photosensitising treatment agents (LC 25 & LC 10 ) are capable of inducing significant changes in the snails' egg laying capacity, sex hormones (progesterone, testosterone and estradiol) and susceptibility to infection with miracidia of S. mansoni.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The authors conjectured that the reason could be disturbances in the activities of the snail enzyme system and the total protein concentration in the tissues and haemolymph which suppressed the development of parasite larval stages in the snail tissues. Similarly, exposure of S. mansoni-infected B. alexandrina to the photosensitiser carbamide perhydrate significantly reduced the cercarial production per treated snail compared to the control snails (Gawish et al 2009). It can be concluded that sub-lethal concentrations of copper chlorophyllin (Cu-chl) and magnesium chlorophyllin (Mg-chl) as photosensitising treatment agents (LC 25 & LC 10 ) are capable of inducing significant changes in the snails' egg laying capacity, sex hormones (progesterone, testosterone and estradiol) and susceptibility to infection with miracidia of S. mansoni.…”
Section: Discussionmentioning
confidence: 91%
“…The photosensitiser hematoporphyrin causes high mortality of B. alexandrina and their eggs after 12 and 21 hours of exposure to this compound, respectively, followed by four hours of exposure to light with irradiance of 450 and 350 W/m 2 (el-sayed & el-sherBini 2006). The reproductive rate (R 0 ) of B. alexandrina is greatly suppressed by carbamide perhydrate due to its negative effect on the snails' glycolytic and glycogenic activities as well as the transaminase and alkaline phosphatase enzymes (Gawish et al 2009). el-hoMMossany & el-sherBini (2011 found that exposure of B. alexandrina to sub-lethal concentrations of hematoporphyrin-coated gold nanoparticles (Hpd GNPs) for 12 hours followed by four hours of light exposure (336.2 W/m 2 ) significantly reduced their reproductive capacity which may suppress schistosomiasis transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there is a continuous need to search for new plant species with ideal molluscicidal properties (Tantawy et al, 2004;Bakry and Hamdi, 2007). Many investigators have studied the molluscicidal activity of certain plants and their extracts (El-Emam et al, 1990;Shalaby and Abdel-Hamid, 1999;Mossalem, 2003;Abdel-Hamid, 2008;Hasheesh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Gastropods have an effective internal defense system consisting of cellular defense factor (Boehmler et al, 1996) and humeral defense factors (Johnston and Yoshino, 1996;Kofta, 1997). Exposure of snails to sub-lethal concentrations of molluscicidal plants resulted in reduction in total number of haemocytes (Sharaf El-Din, 2003;Martin et al, 2006;Souza and Andrade, 2006;El Sayed, 2006;Kamel et al, 2006Kamel et al, , 2007Gawish et al, 2008) and complete damage in their hermaphrodite gland tissues (Henry et al, 1989;Brackenbury, 1999;Al-Qormuti, 2008;Bakry, 2009;Hasheesh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Two papers reviewed the molluscicidal activity of S. sesban leave extracts. 19,20 The studies used different snail species: Bulinus truncatus and Biomphalaria alexandrina. The two snail species were infected with miracidia of Schistosoma haematobium and Schistosoma mansoni respectively.…”
Section: Molluscicidal Activitymentioning
confidence: 99%